2013
DOI: 10.1111/aor.12243
|View full text |Cite
|
Sign up to set email alerts
|

Blood Flow in Hemodialysis Catheters: A Numerical Simulation and Microscopic Analysis of In Vivo‐Formed Fibrin

Abstract: Although catheters with side holes allow high flow rate during hemodialysis, they also induce flow disturbances and create a critical hemodynamic environment that can favor fibrin deposition and thrombus formation. This study compared the blood flow and analyzed the influence of shear stress and shear rate in fibrin deposition and thrombus formation in nontunneled hemodialysis catheters with unobstructed side holes (unobstructed device) or with some side holes obstructed by blood thrombi (obstructed device). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 22 publications
2
38
1
Order By: Relevance
“…This type of microscopy reaches a greater tissue depth when compared to Confocal Laser Scanning Microscopy, and the greater the tissue depth evaluated, the greater the red blood cell and white blood cell concentration, and the smaller the amount of fibrin interconnected to the cells (2) . In another study, a venous thrombus was observed by Two Photon Laser Scanning Microscopy in which the fibrin plate was surrounded by white blood cells close to the inner wall of the catheter opening (3) . This observation was also found in the present study while evaluating a thrombus using Confocal Laser Scanning Microscopy after 5 days of catheter permanence in the patient (Figures 3a and 3c).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This type of microscopy reaches a greater tissue depth when compared to Confocal Laser Scanning Microscopy, and the greater the tissue depth evaluated, the greater the red blood cell and white blood cell concentration, and the smaller the amount of fibrin interconnected to the cells (2) . In another study, a venous thrombus was observed by Two Photon Laser Scanning Microscopy in which the fibrin plate was surrounded by white blood cells close to the inner wall of the catheter opening (3) . This observation was also found in the present study while evaluating a thrombus using Confocal Laser Scanning Microscopy after 5 days of catheter permanence in the patient (Figures 3a and 3c).…”
Section: Discussionmentioning
confidence: 99%
“…Central venous catheters (CVCs) are radiopaque, and made of silicone, polyurethane or teflon. They may have one to three lumens arranged in parallel at the proximal end, and generally have lateral orifices at their distal end (1)(2)(3) . The openings may induce fibrin formation and subsequent thrombus development.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations